PEREMPUAN DALAM PARLEMEN: KUNCI MENUJU KESETARAAN GENDER DAN PEMBANGUNAN BERKELANJUTAN: Kunci Menuju Kesetaraan Gender dan Pembangunan Berkelanjutan - Irwan, Latifa Irsadyah (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2024)
This study aims to analyze the factors influencing the Gender Inequality Index (GII) in Indonesia and the extent of their impact. The variables examined include the proportion of married women who give birth outside of health facilities (MTF), the proportion of women giving birth to their first child under the age of 20 (MHPK20), the female labor force participation rate (PAK), the percentage of legislative seats occupied by women (DPR), and the proportion of female population with senior high school education or higher (SMA). The analysis results indicate that MTF and MHPK20 have a positive effect on GII, while PAK and DPR have a negative effect, and the SMA variable does not significantly influence GII. The study shows that the most significant reduction in GII comes from the representation of women in parliament, highlighting the importance of women's participation.